A companion to social geography - Del Casino, Vincent J.; Del Casino, Vincent J. (Wiley-Blackwell Companions to geography., 2011)
This volume traces the complexity of social geography in both its historical and present contexts, whilst challenging readers to reflect critically on the tensions that run through social geographic thought.